SELECTION OF A TACTICAL ALGORITHM FOR SURGICAL TREATMENT OF CLOSED DUODENAL INJURY (International journal of medical sciences, 2026)
Among closed injuries of the abdominal cavity trauma duodenum (KDP) holds a special place due to the rare, large traumatic severe complications in 60% of operated patients. The aim of the study was choice of the method of surgical treatment and analysis results of surgical treatment in patients with closed trauma of the KDP. The paper analyzes results of treatment 23 patients with a closed duodenal injury. The most common cause of damage KDP was closed to road traffic injury (10 pers. - 43.5%), resulting in catatrauma in 4 (17.4%) patients. In 5 (21.5%) patients injury was received in the workplace, in 1 - sports injury, in 3 - home injury. Depending on the timing of the victims to the hospital after the injury, the size of the defect duodenal wall, level of injury, associated injuries pancreatoduodenal zone defines the principles of surgical treatment for injuries of the duodenum. According to the grade of damage (I-IV) the most suitable tactic was chosen, including mobilizations, duodenal decompression, hematoma evacuation, gastroenteroanastomosis etc. The volume of surgery at closed duodenal injury must be selected individually, depending on the severity of the injury and status of victim. In the postoperative period is mandatory drug suppression of secretion digestive tract and the appointment of broad-spectrum antibiotics against background of infusion-transfusion therapy.